Pengaruh Status Sosial Ekonomi Orang Tua Terhadap Tingkat Pendidikan Anak - Fahira Fahmi; Yannefri Bakhtiar; Amiruddin Saleh; Abdul Fat-Han Ismail; Sang Ayu Made Sri Tandewi; Fazrina Andriani Sakinah Lubis; Devi Nur Faddhila Silitonga; Difa Maulina Syahidah; Fakhry Khotibul Umam; Muhammad Izzul Fikri Noor; Muhammad Sabilal Muhajirin; Silvi; Siski Andini Sukowati; Siti Julaeha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Education is not only a matter of things in school but also of things outside the school. Familyand parents are the place where the children can get their first education so that their role is very bigin their children's education going forward. The purpose of this study is to analyze the effect ofparents' socio-economic status on children's education levels in Neglasari. This study uses aqualitative approach with in-depth interview techniques. The data collection technique was snowballand the data presented were in the form of primary data that results analyze from interviews withrespondents. The results showed that the socio-economic status of parents in Neglasari did not affectthe level of children's education but motivation from the children and parents' concern for children'seducation influenced the level of children's education.